The Benefits and Costs of Intervening in Banking Crises - Frydl, Edward (IMF Working Papers; Working Paper ;, 2000)
This paper provides a framework to assess the benefits and costs of intervening in a banking crisis. Intervention involves liquidity support and resolution actions. Principal benefits of intervention include avoiding panic and eliminating the economic costs of distorted incentives. Principal costs include fiscal costs and the economic costs of delay. The government's main decision concerns the length of the resolution horizon-whether to adopt a deliberate or an aggressive resolution strategy. Dominant factors affecting net benefits are the relative size of the banking system and the loss liquidation rate on assets financed by bank loans.